Cytochrome 1A1 and 1B1 gene diversity in the Zanzibar islands - Cavaco, I. (2018)
Amodiaquine (AQ) is a 4-aminoquinoline widely used in the treatment of malaria as part of the artemisinin combination therapy (ACT). AQ is metabolised towards its main metabolite desethylamodiaquine mainly by cytochrome P450 2C8 (CYP2C8). CYP1A1 and CYP1B1 play a minor role in the metabolism but they seem to be significantly involved in the formation of the short-lived quinine-imine. To complete the genetic variation picture of the main genes involved in AQ metabolism in the Zanzibar population, previously characterised for CYP2C8, we analysed in this study CYP1A1 and CYP1B1 main genetic polymorphisms. The results obtained show a low frequency of the CYP1A1*2B/C allele (2.4%) and a high frequency of CYP1B1*6 (approximately 42%) followed by CYP1B1*2 (approximately 27%) in Zanzibar islands. Genotype data for CYP1A1 and CYP1B1 show a low incidence of fast metabolisers, revealing a relatively safe genetic background in Zanzibars population regarding the appearance of adverse effects.